Neglected child with substance abuse leading to child abuse: A case report - Subramanian E; Subhagya B; Muthu M; Sivakumar N (Wolters Kluwer Medknow Publications, 2005)
Child abuse and neglect is any interaction or lack of interaction between a caregiver and a child resulting in nonaccidental harm to the child′s physical and developmental state. Substance abuse is ingestion of any drug, which is capable of altering the mental functioning eventually leading to addiction. This paper presents a case report of a 12-year-old neglected girl with substance abuse for which she was physically abused by her mother.